Finding Genetic Variation in Soybean (Glycine max (L.) Merrill) Flowering Time by Simple Sequence Repeat Marker - Ngon, Truong Trong; Lee, Suk-Ha (Research Perspectives of Microbiology and Biotechnology Vol. 1, 2024)
Flowering time is one of the important target traits in a soybean breeding program. Photoperiod and temperature influence the vegetative and reproductive development from emergence to maturity in soybean. The objective of this study was to analyze genetic variation in flowering time based on agronomic performance and SSR marker. About 108 soybean cultivars were used for this study. Eight primers relating flowering genes were selected based on soybean cDNA library from NCBI and TIGR. These primers were designed by using Primer 3 [1] to amplify fragments of 500-800bp. The optimum melting temperature was observed for each primer between 58o to 68oC. PCR was followed by protocol of Crop Genomics Laboratory. PCR products producing a single discrete band were purified by AccuPre\(\circledR\) PCR purification kit (Bioneer, Korea). The purified PCR product was directly sequenced using one of the PCR primers with BigDye Terminator Cycle Sequenceing Kit (Applied Biosystems, Foster City, CA, USA). The labeling reaction mixture was ethanol-preciputated, and resuspended in 10\(μ\)l of water. The sequence was analyzed using ABI 3700 sequencer (Applied Biosystems, Foster City, CA, USA). In conclusion, there was wide variation in flowering time of soybean. Gene diversity at nucleotide level will be useful for breeders to make strategy for soybean improvement in future.